Design and fabrication of automatic fish feeder / Muhammad Ibrahim Nor Azman - Nor Azman, Muhammad Ibrahim (2023)
Having fish as pets nowadays is a really common thing, no matter if you are rich or not. Feeding pets is important to make sure they can get enough nutrients and live healthily. The automatic fish feeder is introduced to make sure pets are provided with enough food consistently without you having to consistently monitor them. Automatic fish feeders that are available in the market nowadays are pretty expensive and not much are being sold and produced in the common marketplace. Apart from that, they require a large amount of electricity to run and operate. So, this project introduces a new prototype that has no electricity consumption at all. It is also cheap, easy to use and installed due to lack of complicated mechanism